Revitalizing education through the integration of cloud technologies - Valerii Yu. Bykov (Academy of Cognitive and Natural Sciences, 2023)
Objective: This research aims to identify the strategic direction for modernizing the education system in Ukraine through the integration of cloud computing technology. Methods: The study utilizes analysis and forecasting to examine the current trends in education system modernization and the role of information and communication technologies. It focuses on identifying strategic areas for implementing cloud computing technology in Ukrainian education. Research focus: The research explores the theoretical and methodological foundations of using cloud computing technology as a means to modernize the education system in Ukraine. Results: The analysis reveals that the successful implementation of a modern educational paradigm, based on the principles of open education, requires comprehensive informatization of the national education system. The study highlights key tools of open education that significantly enhance teaching effectiveness. It also examines the evolution of information and communication technology networks in education, emphasizing the potential for radical improvement in content and technology through ICT integration. The role of cloud computing technology and ICT outsourcing in educational organization is discussed, along with strategic areas for education informatization in Ukraine. Conclusions and recommendations: Technological and organizational solutions are crucial for addressing important societal challenges and fostering progressive development. Practical application of these solutions will accelerate scientific and technological progress and contribute to the transition towards a knowledge-based society, advancing humanity's future.